2016
DOI: 10.1530/eje-16-0528
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of subclinical inflammation and increases in glycaemia, insulin resistance and beta-cell function in non-diabetic individuals: the Whitehall II study

Abstract: Objective: Higher systemic levels of pro-inflammatory biomarkers and low adiponectin are associated with increased risk of type 2 diabetes, but their associations with changes in glycaemic deterioration before onset of diabetes are poorly understood. We aimed to study whether inflammation-related biomarkers are associated with 5-year changes in glucose and insulin, HbA1c, insulin sensitivity and beta-cell function before the diagnosis of type 2 diabetes and whether these associations may be bidirectional. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 42 publications
5
40
1
1
Order By: Relevance
“…These findings were almost concordant with previous reports [36,37]. Festa et al [36] reported that inflammation in the prediabetic state was related to increased insulin resistance rather than decreased insulin secretion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were almost concordant with previous reports [36,37]. Festa et al [36] reported that inflammation in the prediabetic state was related to increased insulin resistance rather than decreased insulin secretion.…”
Section: Discussionsupporting
confidence: 92%
“…Festa et al [36] reported that inflammation in the prediabetic state was related to increased insulin resistance rather than decreased insulin secretion. Herder et al [37] have recently reported that higher hs-CRP and interleukin (IL)-6 were associated with increases in fasting insulin and insulin resistance and IL-6 (but not hs-CRP) was associated with HOMA-β. Although we have no data on IL-6, it has been reported that IL-6 can stimulate insulin secretion through glucagon-like peptide-1 (GLP-1) production and secretion in animal models of type 2 diabetes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term alterations in the regulation of the HPA axis and its final product, cortisol, are a known consequence of the enormous stress caused by maltreatment during childhood (Carpenter et al, 2007), and are linked to health outcomes such as cancer and cardiovascular and metabolic diseases (Kumari, Shipley, Stafford, & Kivimaki, 2011; Volden & Conzen, 2013). Furthermore, chronic inflammatory processes, encompassing increased levels of pro-inflammatory cytokines and oxidative stress, are a demonstrated long-term consequence of child maltreatment (Boeck et al, 2016) and are known to play a role in the pathomechanisms of cancer (Taniguchi & Karin, 2018), cardiovascular diseases (Harrington, 2017), diabetes and other metabolic diseases (Herder et al, 2016). As well as biological mechanisms, socioeconomic and behavioural aspects are considered to be relevant for the demonstrated link between child maltreatment and health conditions in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The close association of systemic inflammation with cardiovascular diseases (CVD) and metabolic syndrome is a recent topic in medicine (1-3). Inflammatory skin diseases such as psoriasis are an integral part of diseases causing systemic inflammation (4).…”
Section: Introductionmentioning
confidence: 99%